Taxonomic revision of New World species of the genus Oosternum Sharp (Coleoptera: Hydrophilidae: Sphaeridiinae) I. Definition of species groups and revision of the Oosternum aequinoctiale group - Fikáček, Martin; Hebauer, Franz; Hansen, Michael (Zootaxa, 2009)
The genus Oosternum Sharp, 1882 is divided into ten species groups based on external adult characters. An identification key to the species groups and a table of diagnostic characters as well as many charater state illustrations for each group are provided. Representatives of the newly defined O. aequinoctiale species group are revised. Six species of this group are recognized, all occurring in the Neotropical region: Oosternum acutheca sp.n. (Honduras, Costa Rica, Nicaragua), O. aequinoctiale (Motschulsky, 1855) (Bolivia, Colombia, Costa Rica, Ecuador, Mexico, Panama, Peru, Venezuela), O. attenuatum sp. n. (Panama, Colombia, Ecuador), O. gibbicolle sp. n. (Ecuador, Panama), O. holosericeum sp. n. (Argentina), and O. latum sp. n. (Lesser Antilles: St. Vincent Island). A key to the species and drawings or SEM photographs of diagnostic characters are provided.